Effect of varying ratios of oyster mushroom powder to tapioca flour on the physicochemical properties and sensory acceptability of fried mushroom crackers - Faridah Yahya,; Noor Nadzirah Mat Yusof,; Chan, Kai Chen (Penerbit Universiti Kebangsaan Malaysia, 2017)
The objective of this study was to determine the effect of different ratios of powder prepared from oyster mushroom to tapioca flour on the physicochemical properties and sensory acceptability of fried mushroom crackers. Four recipes for crackers were formulated with varying ratios of oyster mushroom powder to tapioca flour, i.e. 5:95; 10:90; 15:85 and 20:80. The control sample comprised 100% tapioca flour. Sensory acceptability was performed using an affective test on a 7-point hedonic scale. Fried mushroom crackers showed significant decreases (p<0.05) in the L* value, oil absorption and hardness, while the b* value, linear expansion, ash and protein contents increased when the content of oyster mushroom powder was increased in the crackers. Sensory acceptability of the crackers was significantly improved (p<0.05) with the addition of oyster mushroom powder as compared with the control. Crackers made with 15% of oyster mushroom powder and 85% of tapioca flour gave the highest mean score in all the evaluated sensory attributes; they were not significantly different (p>0.05) in these respects from crackers containing 20% oyster mushroom powder. These results can be useful in the development of vegetarian fried mushroom crackers that may serve as an alternative to crackers more commonly based on fish or other seafood.